Hand and wrist orthoses for adults with rheumatological conditions: practice guidelines for occupational therapists - College of Occupational Therapists (Royal College of Occupational Therapists, 2015)
Effective self-management, in conjunction with collaborative multidisciplinary team management in rheumatoid arthritis and osteoarthritis, requires clients to make multiple changes and teams to provide multiple interventions. To maximise effective service delivery, these must be evidence-based.